In This World of Ultraviolet Light : Stories - Palma, Raul (Book collections on Project MUSE., 2023)
""These are new Cubans. Twenty-first-century Marielitos. Balseros, as the bartender had referred to them. I know, because my mom tells me that these are the kinds of Cubans I need to stay away from." In eight captivating stories, In This World of Ultraviolet Light navigates tensions between Cubans, Cuban Americans, and the larger Latinx community. Though these stories span many locations-from a mulch manufacturing facility on the edge of Big Cypress National Preserve to the borderlands between Georgia and the Carolinas-they are overshadowed by an obsession with Miami as a place that exists in the popular imagination. Beyond beaches and palm trees, Raul Palma goes off the beaten path to portray everyday people clinging to their city and struggling to find cultural grounding. As Anjali Sachdeva writes, "This is fiction to steal the breath of any reader, from any background." Boldly interrogating identity, the discomfort of connection, and the entanglement of love and cruelty, In This World of Ultraviolet Light is a nuanced collection of stories that won't let you go"--